BABY SWAP AS DRAMATIC IRONY: A PLOT TECHNIQUE IN ONYEKAONWU’S ERIRI MAARA NGWUGWU (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study explores how dramatic irony is used by the playwright to reveal to the readers or audience the ignorance of a character who acts in a way recognized as a grave mistake in Eriri Mara Ngwugwu. The study researches baby swap as dramatic irony used in the development of plot in Onyekaonwu’s Eriri Mara Ngwugwu. It showcases how it was used as dramatic irony in moving the story forward. Hence, this study presents a detailed analysis of baby swapping, importance and usefulness of dramatic irony in literary work. In employing this technique,  Onyekaonwu created characters with varying dispositions who cannot see or understand the contrast of their thoughts and actions. Dramatic irony can be used as an amusing exposure of a character’s stupidity. Sometimes it could be used to cause anger and hatred or to show tragedy and sadness. This research, therefore, aims at exploring dramatic irony, illustrating the creativity and effectiveness of baby swap as plot technique in a classic Igbo play. It further reveals how the writer creatively used this technique to create conflict, suspense, thus enhancing the reader’s understanding of the Igbo concept of tragedy as evident in the play.
Keywords: BabySwap,DramaticIrony,Plot,Technique,Play